The Soldier Writer: Configurations of an Ideal Identity in the Stories of Colombian Literature Diana (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
The figure of the soldier writer in literature stories constitutes a foundationalparadigm in the construction of the idea about the Latin-American intellectual. Such paradigm is the object of a dynamic that we named the circle of metamorphosis, which evidences the process that begins with the soldier writer in battle ––represented by Gonzalo Jiménez de Quesada–– and ends with the hero writer as a constructer of public opinion and narrator of national history. All these images take part in the construction of national identity and in the ideal of the Latin-American intellectual linked to the battle and performance characteristics of Emancipation. Thus, this article aims to open the door for future discussions around the rol of literature stories insidethe social and historical development of the continent.
Keywords: nation; intellectual; independence; writer; soldier; hero